Food security in sub-Saharan Africa: a fresh look on agricultural mechanisation. How adapted financial solutions can make a difference - Christiane Ströh de Martínez; Marietta Feddersen; Anna Speicher (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
Much of sub-Saharan Africa's farmland is (still) cultivated with the hand hoe, and agricultural processing and transport are often done manually. This limits the potential of agriculture in the region. Mechanisation can help to alleviate food shortages and enhance agricultural development. However, this implies high levels of investment for farmers and some risks for rural populations and eco-systems. The necessary financing is especially difficult to access and risky for longer-term agricultural investments such as mechanisation. In addition, there can be trade-offs between mechanisation and employment. To better understand how mechanisation can contribute to food security, this study first assesses the controversial impact of mechanisation on rural populations and their environments. In a second step, the difficulty in accessing financing is analysed, distilling success factors for financing mechanisation. Thereby, the study aims at bringing the sectors of agriculture and finance closer together with the overall objective of fighting food insecurity in sub-Saharan Africa.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Landwirtschaft und ländliche Entwicklung